Perfect adaptation of CD8(+) T cell responses to constant antigen input over a wide range of affinities is overcome by costimulation - Trendel, N; Kruger, P; Gaglione, S; Nguyen, J; Pettmann, J; Sontag, ED; Dushek, O (American Association for the Advancement of Science, 2021)
Maintaining and limiting T cell responses to constant stimulation with antigen are critical to control pathogens and maintain self-tolerance, respectively. Antigen recognition by T cell receptors (TCRs) activates signaling that stimulates T cells to produce cytokines and also leads to the down-regulation of cell surface TCRs. In other systems, receptor down-regulation can induce perfect adaptation to constant stimulation by a mechanism known as state-dependent inactivation, which requires complete down-regulation of the receptor or the ligand; however, this is not the case for the TCR. Here, we observed that in vitro–expanded primary human T cells exhibited perfect adaptation with respect to cytokine production to constant antigen stimulation across a 100,000-fold variation in affinity with partial TCR down-regulation. By directly fitting a mechanistic model to these data, we showed that TCR down-regulation produced imperfect adaptation, but, when coupled to a switch, produced perfect adaptation in terms of cytokine production. A prediction of this model was that TCR signaling induced by peptide-bound major histocompatibility complex (pMHC) continues after adaptation, which we confirmed by showing that, whereas costimulation could not prevent adaptation, signaling by the costimulatory receptors CD28 and 4-1BB reactivated adapted T cells to produce cytokines in a pMHC-dependent manner. We showed that adaptation also applied to first-generation chimeric antigen receptor (CAR) T cells but was partially avoided with second-generation CARs. These findings highlight that perfect adaptation limits the responses of T cells, rendering them dependent on costimulation for sustained responses.